Personalized Anti-Retroviral Treatment Alleviates Viral Loads among HIV-AIDS Patients in Papua - Widayanti Linda Prasetyaning; Andiarna Funsu; Khoiriyah Romyun Alvy; Oktorina Sarita; Andyarini Esti Novi; Tyastirin Esti; Widiyanti Mirna (BIO Web of Conferences)
HIV/AIDS is a disease that causes secondary immunodeficiency and has now become a global issue. The prevalence of HIV/AIDS in Indonesia is 558,618 cases. Papua Province recorded 41,286 HIV cases, with 24,873 AIDS cases. This study aimed to analyze the potential risk factors for the reduction of viral load in Anti Retroviral Therapy profiles in HIV patients in Papua. This research used an observational analytic study with a cross-sectional approach. Respondents were sampled from 6 hospitals in Papua. Data analysis was conducted using logistic regression. The results of this study indicated that Anti Retroviral Therapy had a significant effect (p=0.000) on the reduction of viral load through the detection of CD4 levels in HIV/AIDS patients. Anti Retroviral Therapy requires consideration of the sociodemographic and genetic characteristics of each patient to optimize the success of the HIV/AIDS program.